(untitled) (Texas Journal of Engineering and Technology, 2022)
The problem of teaching students’ oral speech at foreign language lessons, which arose under the influence of the "backwash effect" of language tests on the content and form of the lessons of a foreign language educational course, is considered. Under the influence of language tests in the classroom, the practice of performing language tasks in the form of filling out forms of various types has become widespread, while the communicative activity of students has gradually lost its status of significance. As a result, in the classroom, the speaking time of students was noticeably reduced, as a result, the level of oral speech skills decreased, teachers began to pay more and more attention and time to language training, replacing speech competence with a test one.